PENGARUH DIGITALISASI PADA SISTEM KENDALI - Wahjudi, Rudy S (Jurnal Teknik Elektro, 2003)
Digital computers are available not only for design of control system but also to perform thecontrol function. Advances in digital computers and microprocessors have made their usevery attractive as components in control system. Using digital computer with a plantoperating in the continuous-time domain requires that its input signal be discrete, which inturn requires the sampling of the signals used by the controller. An A/D converter must beincorporated in the digital control system. This paper presents the choice of sampling timeand bit numbers and theyâre to the system characteristics. An example of the calculation ofsampling time an. their results are presented in the paper.Keywords: digital computer, sampling theorem and A/D converter.1. Pendahuluan